ANALISIS PERILAKU EKSPLORATIF DAN GROWTH MINDSET MURID SEKOLAH DASAR DALAM MEMECAHKAN MASALAH MELALUI PERMAINAN LEGO - Mona Yulia; Sutrisno, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This qualitative descriptive study aims to analyze the exploratory behavior and growth mindset profile of elementary school students while solving an authentic structural-engineering problem through lego block play. The study addresses a gap in the literature, given that most existing research on constructive block play concentrates on early childhood cognitive and social-emotional outcomes, while empirical evidence on exploratory problem-solving behavior and growth mindset among upper-grade elementary students remains limited. Six fifth-grade students were purposively selected and engaged in an individual free-construction task, followed by a collaborative “Structure Detective” mission requiring them to design a lego bridge that met defined engineering constraints. Data were collected through a five-indicator behavioral observation rubric (curiosity, fluency, flexibility, resilience, and independent trial-and-error), semi-structured interviews built on growth mindset indicators, and reflective journals, then analyzed using the Miles and Huberman interactive model with source triangulation. Findings indicate that most students displayed well-developed exploratory behavior, particularly resilience after structural collapse, and expressed beliefs consistent with a growth mindset, such as preferring challenging tasks, persisting after failure, and treating mistakes as a source of learning. Two students demonstrated exploratory behavior from the outset, three others required a brief warm-up period before engaging spontaneously, and one student displayed a mixed mindset profile that combined effort attribution with residual fixed beliefs about innate ability. The study concludes that open-ended, low-stakes lego-based engineering challenges can serve as an effective pedagogical medium for cultivating twenty-first-century problem-solving dispositions in the elementary classroom.